Knowledge and attitudes of health care workers from intensive care units regarding nosocomial transmission of influenza: A study on the immediate pre-pandemic period - Fortaleza, C. R.; Fortaleza, C. M.C.B. [UNESP] (FapUNIFESP (SciELO), 2011)
The transmission of influenza in health care settings is a major threat to patients, especially those with severe diseases. The attitude of health care workers (HCWs) may influence the transmission of countless infections. The current study aimed to quantify knowledge and identify attitudes of HCWs involved in intensive care units (ICUs) regarding the risk of nosocomial influenza transmission. A questionnaire was applied through interviews to HCWs who worked in one of the five ICUs from a teaching hospital. Questions about influenza were deliberately dispersed among others that assessed several infectious agents. Forty-two HCWs were interviewed: nine physicians, ten nurses and 23 nursing technicians or auxiliaries. Among the 42 HCWs, 98% were aware of the potential transmission of influenza virus in the ICUs, but only 31% would indicate droplet precautions for patients with suspected infection. Moreover, only 31% of them had been vaccinated against influenza in the last campaign (2008). Nursing technicians or auxiliaries were more likely to have been vaccinated, both by univariate and multivariable analysis. When asked about absenteeism, only 10% of the study subjects stated that they would not go to work if they had an influenza-like illness. Those findings suggest that, in non-pandemic periods, influenza control in hospitals requires strategies that combine continuous education with changes in organizational culture. © CEVAP 2011.
Keywords: Health care workers; Health care-acquired infections; Influenza; Intensive care units; Vaccination